2011
DOI: 10.1093/cvr/cvr308
|View full text |Cite
|
Sign up to set email alerts
|

Nox1 transactivation of epidermal growth factor receptor promotes N-cadherin shedding and smooth muscle cell migration

Abstract: The Nox1 NADPH oxidase signals through EGFR to activate MMP-9 and promote the shedding of N-cadherin, thereby contributing to SMC migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 41 publications
(59 reference statements)
0
53
1
Order By: Relevance
“…Therefore, the diverse roles of NOX isoforms in this complex signaling pathway likely depend on the stage of EGFR activation or on OCTOBER 28, 2016 • VOLUME 291 • NUMBER 44 specific subcellular events after EGFR/Src internalization or trafficking localization. Moreover, the relative role(s) of DUOX1 or other NOX isoforms may also depend on the cell type, highlighted by previous studies showing a role for NOX1 in Src-dependent transactivation of EGFR in vascular smooth muscle cells (25). Nevertheless, our findings indicate that EGFR activation in airway epithelial cells is associated with combined oxidative mechanisms initiated by activation of both DUOX1 and NOX2, which both contribute to cysteine oxidation within EGFR and Src.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore, the diverse roles of NOX isoforms in this complex signaling pathway likely depend on the stage of EGFR activation or on OCTOBER 28, 2016 • VOLUME 291 • NUMBER 44 specific subcellular events after EGFR/Src internalization or trafficking localization. Moreover, the relative role(s) of DUOX1 or other NOX isoforms may also depend on the cell type, highlighted by previous studies showing a role for NOX1 in Src-dependent transactivation of EGFR in vascular smooth muscle cells (25). Nevertheless, our findings indicate that EGFR activation in airway epithelial cells is associated with combined oxidative mechanisms initiated by activation of both DUOX1 and NOX2, which both contribute to cysteine oxidation within EGFR and Src.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, recent studies from our group revealed that EGFR transactivation in airway epithelial cells by initial activation with ATP of purinergic GPCRs, due to epithelial injury or exposure to environmental allergens, is associated with enhanced cysteine oxidation within Src as well as EGFR, depending on activation of the NADPH oxidase homolog dual oxidase 1 (DUOX1) (22)(23)(24). Other studies indicate a comparable role for NOX1 in EGFR transactivation in vascular smooth muscle cells in response to thrombin (25). Alternatively, recent studies by Carroll and co-workers (16) indicated that EGF-dependent activation of EGFR in epidermoid carcinoma A431 cells involves cysteine oxidation within the EGFR kinase domain mediated by ROS generated from the NADPH oxidase NOX2.…”
Section: From the Department Of Pathology And Laboratory Medicine Unmentioning
confidence: 99%
“…Moreover, it has been reported that endogenous hydrogen peroxide (H 2 O 2 ), produced as a consequence of EGF binding to EGFR, can be utilized by the cells as a secondary messenger to regulate physiological signal transduction (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…It not only plays an important physiological role in processes such as cellular migration and apoptosis, but also its deregulation can cause pathological states such as cancer. Transactivation of various growth factor receptors, including epidermal growth factor receptor (EGFR), by GPCRs has been documented in multiple cellular model systems, hence demonstrating the potential role of GPCRs in tumor tropism via receptor transactivation ( Jagadeesha, Takapoo, Banfi, Bhalla, & Miller, 2012;Maretzky et al, 2011;Yahata et al, 2006). A commonly reported mechanism of receptor transactivation involves the activation of membrane-tethered growth factors, such as EGFR, through direct interaction with GPCRs, such as CXCR4 (Porcile et al, 2005).…”
Section: Stem Cell Homing and Migrationmentioning
confidence: 99%